Habituation and spatial memory in the context of emotional regulation: Behavioral and genetic mechanisms underlying context information-processing and de-arousal grooming - Rojas Carvajal, Mijail (2017)
Habituation is the ability to passively reduce a response after repeated or prolonged exposures to a particular stimulus. From a cognitive perspective, habituation is a basic, information-gating process that contributes to filter out irrelevant information in order to focus cognitive sources on a specific goal. In higher order capabilities as in spatial memory, a similar process takes place with the purpose of facilitate navigation towards the target place. In rodents, some forms of physical and social stimulation, like environmental enrichment (EE), potentiate both habituation and spatial memory. Here, we examined whether habituation capacity predicts spatial memory in the Barnes maze test (BMT). Male Wistar rats were kept for 30 days either on EE or on standard housing. During that time, half of the animals within each group were tested weekly in a 15-min open-field test (OFT) with the aim to explore long-term habituation. After the housing period, all rats were tested during four consecutive days in the OFT to assess short-term habituation. Afterwards, a three-day BMT protocol was used to evaluate several spatial and non-spatial memory parameters. To assess some brain mechanisms related with memory formation and brain plasticity, the hippocampal mRNA levels of BDNF, CREB, and p250GAP genes were evaluated. Evidence about the effects of EE on short-term and long-term OFT habituation and on BMT will be provided. We will show the likely contribution of OFT behaviors, including certain types of grooming behavior, as predictors of spatial memory. Also, the association between gene expression and behavioral parameters will be presented. Because non-associative memory is observed in a plethora of species as a first-level mechanism of information processing, elucidating its functions could shed some light to better understand the complex interplay of cognitive systems.